A novel method for in vivo measurement of dynamic ischiofemoral space based on MRI and motion capture - Wang, Yining; Ma, Dong; Feng, Zhengkuan; Yu, Wanqi; Chen, Yanjun; Zhong, Shizhen; Ouyang, Jun; Qian, Lei (Frontiers in Bioengineering and Biotechnology, 2023)
PURPOSE: To use a novel in vivo method to simulate a moving hip model. Then, measure the dynamic bone-to-bone distance, and analyze the ischiofemoral space (IFS) of patients diagnosed with ischiofemoral impingement syndrome (IFI) during dynamic activities. METHODS: Nine healthy subjects and 9 patients with IFI were recruited to collect MRI images and motion capture data. The motion trail of the hip during motion capture was matched to a personalized 3D hip model reconstructed from MRI images to get a dynamic bone model. This personalized dynamic in vivo method was then used to simulate the bone motion in dynamic activities. Validation was conducted on a 3D-printed sphere by comparing the calculated data using this novel method with the actual measured moving data using motion capture. Moreover, the novel method was used to analyze the in vivo dynamic IFS between healthy subjects and IFI patients during normal and long stride walking. RESULTS: The validation results show that the root mean square error (RMSE) of slide and rotation was 1.42 mm/1.84° and 1.58 mm/2.19°, respectively. During normal walking, the in vivo dynamic IFS was significantly larger in healthy hips (ranged between 15.09 and 50.24 mm) compared with affected hips (between 10.16 and 39.74 mm) in 40.27%–83.81% of the gait cycle (P=0.027). During long stride walking, the in vivo dynamic IFS was also significantly larger in healthy hips (ranged between 13.02 and 51.99 mm) than affected hips (between 9.63 and 44.22 mm ) in 0%–5.85% of the gait cycle (P=0.049). Additionally, the IFS of normal walking was significantly smaller than long stride walking during 0%–14.05% and 85.07%–100% of the gait cycle (P=0.033, 0.033) in healthy hips. However, there was no difference between the two walking among the patients. CONCLUSIONS: This study established a novel in vivo method to measure the dynamic bone-to-bone distance and was well validated. This method was used to measure the IFS of patients diagnosed with IFI, and the results showed that the IFS of patients is smaller compared with healthy subjects, whether in normal or long stride walking. Meanwhile, IFI eliminated the difference between normal and long stride walking.